Load flow programming by using C++ / Saiful Azmin Abdul Wahid - Abdul Wahid, Saiful Azmin (2002)
This paper represent the title of the load flow programming by using C++. The load flow or in another name as power flow is the solution for the normal steady-state operating conditions of an electric power system.